The Great Diseases Project: A Partnership between Tufts Medical School and the Boston Public Schools - Jacque, Berri (2013)
Medical schools, although the gatekeepers of much biomedical education and research, rarely engage formally with K-12 educators to influence curriculum content or professional development. This segregation of content experts from teachers creates a knowledge gap that limits inclusion of current biomedical science into high school curricula, impacting both public health literacy and the biomedical pipeline. The authors describe how, in 2009, scientists from Tufts Medical School and Boston public school teachers established a partnership of formal scholarly dialog to create 11(th)–12(th) grade high school curricula about critical health-related concepts, with the goal of increasing scientific literacy and influencing health-related decisions. The curricula are based on the great diseases (infectious diseases, neurological disorders, metabolic disease, and cancer). Unlike most health science curricular interventions that provide circumscribed activities, the curricula are comprehensive, each filling one full term of in-class learning and providing extensive real-time support for the teacher. In this article, the authors describe how they developed and implemented the infectious disease curriculum, and its impacts. The high school teachers and students showed robust gains in content knowledge and critical thinking skills, while the Tufts scientists increased their pedagogical knowledge and appreciation for health-related science communication. The results show how formal interactions between medical schools and K-12 educators can be mutually beneficial.